2008
DOI: 10.2174/187152808784165225
|View full text |Cite
|
Sign up to set email alerts
|

Liver Tolerance and the Manipulation of Immune Outcomes

Abstract: In recent years it has become apparent that the liver holds a distinct immunological position. Previously described as a "graveyard" for T cells activated in the periphery, emerging evidence indicates that this organ may have a more active role in mediating tolerance. Attenuated immune responses in the liver can be beneficial in the transplantation setting, as liver transplants are more readily accepted than other organ allografts even in the absence of immunosuppressive drugs. However, the ability of the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 105 publications
(167 reference statements)
0
12
0
Order By: Relevance
“…These results showed that, after low-dose rAAV treatment, direct activation of OT-I T cells exclusively by OVA-expressing hepatocytes was able to prime CTLs by week 1 and that these CTLs were not silenced at week 3. It was unexpected that hepatocytes could induce OT-I development into cytotoxic effectors by direct-presentation, as we have shown consistently in the past that naive CD8 Des T cells exclusively activated by hepatocytes developed poor CTL function and/or died prematurely, resulting in undetectable CTL activity in vivo (18). However, the outcome of intrahepatic Des T-cell activation had never been assessed in the setting of low H-2K b antigen expression.…”
Section: A Threshold In the Number Of Antigen-expressing Hepatocytesmentioning
confidence: 99%
“…These results showed that, after low-dose rAAV treatment, direct activation of OT-I T cells exclusively by OVA-expressing hepatocytes was able to prime CTLs by week 1 and that these CTLs were not silenced at week 3. It was unexpected that hepatocytes could induce OT-I development into cytotoxic effectors by direct-presentation, as we have shown consistently in the past that naive CD8 Des T cells exclusively activated by hepatocytes developed poor CTL function and/or died prematurely, resulting in undetectable CTL activity in vivo (18). However, the outcome of intrahepatic Des T-cell activation had never been assessed in the setting of low H-2K b antigen expression.…”
Section: A Threshold In the Number Of Antigen-expressing Hepatocytesmentioning
confidence: 99%
“…In the absence of a spleen, transfused RBCs are shunted to the liver, an organ thought to be more tolerogenic than immunogenic [105]. Recent studies in mice have demonstrated that a spleen is critical for primary immune responses to transfused RBCs [106], though non-responsiveness may not equate to long-term tolerance.…”
Section: Recipient Factorsmentioning
confidence: 99%
“…The liver holds a distinct cellular and molecular environment [20] and structural changes of tumor microenvironment of CRC often occur once metastasize to the liver [21]. Recent studies have demonstrated the involvement of MSCs as an important cellular element within tumor microenvironments [22].…”
Section: Discussionmentioning
confidence: 99%